Pengaruh Kompres Hangat Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif - S, Suprida; R, Rohaya; Nursanti, Rina; Setiawati, Desi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background: Labor is the process of expelling a viable product of conception from the uterus through the vagina into the outside world (Kuswanti, 2014:1). Normal labor is characterized by uterine contractions that cause cervical effacement and dilation and push the fetus through the birth canal, resulting in pain experienced by the mother. Pain causes suffering and stress, which, if not relieved, can influence subsequent pain responses. Objective: To determine the frequency distribution of pain levels among women in the active phase of the first stage of labor before the application of warm compresses at an independent midwifery practice (BPM) in Palembang City. Methods: This study employed an experimental research method, namely a study involving an intervention to determine its effect (Notoatmodjo, 2013, p. 50). The research design was a pre-experimental design using a one-group pretest–posttest approach, in which a pretest (O1) was conducted, followed by an intervention (X), and then a posttest (O2) in the same group. Results: Labor pain is a manifestation of uterine muscle contractions (shortening). These contractions cause pain in the lower back and abdominal area and may radiate to the thighs. The contractions also result in cervical dilation, which enables the birth process to occur. Effective management of labor pain is essential to provide comfort to the mother during childbirth, as this is part of respectful maternity care and reflects the roles and functions of midwives. Conclusion: Based on the Wilcoxon test, a significance (? value) of 0.000 was obtained, indicating that ? ? 0.05. This result shows that the application of warm compresses has a significant effect on reducing pain intensity in women during the active phase of the first stage of labor at BPM Fauziah Hatta, Mala Husin, and Bakiah Azhar in 2024.